PENGARUH HARGA BATUBARA, KURS RUPIAH, DAN PENDAPATAN TERHADAP NILAI SAHAM PADA PT. ADARO ENERGY INDONESIA (PERSERO), Tbk - Khairuddin Khairuddin; Muhammad Farhan Noor (POLITEKNIK LP3I JAKARTA, 2025)
The main problem identified is the instability of assets due to several factors that may be caused by certain variables at PT. Adaro Energy Indonesia (Persero) Tbk. The purpose of this research is to analyze and determine the simultaneous influence of coal prices, rupiah exchange rate, and revenue on the stock value of PT. Adaro Energy Indonesia (Persero) Tbk, from 2018 to 2023. The method applied by the researcher is quantitative, which is used to investigate a specific population or sample, with data collection using research instruments, and data analysis being quantitative or statistical in nature, aimed at testing the established hypotheses. The quantitative method is developed with an associative approach where this research questions the relationship between two or more variables. The population used in this research is the financial reports of PT. Adaro Energy Indonesia (Persero) Tbk for the period of 2018 – 2023 (6 years). From these financial reports, monthly data is used, amounting to a total sample of 72 months. The results of this study indicate that Coal Prices (X1), Rupiah Exchange Rate (X2), and Revenue (X3) simultaneously or collectively have a positive and significant influence on Stock Value (Y).